Harnessing the power of social media for academic networking and collaboration / Zuraidah Arif and Zati Atiqah Mohamad Tanuri - Arif, Zuraidah; Mohamad Tanuri, Zati Atiqah (Universiti Teknologi MARA, Kedah, 2024)
The academic landscape is evolving rapidly, driven by the digital revolution and the influence of social media platforms. These digital tools have redefined how scholars engage with their research, peers, and the global academic community. The integration of social media in academia has ushered in a multitude of advantages, transforming the conventional modes of research dissemination, collaboration, and knowledge exchange. This paper explores the multifaceted benefits of social media for academics, highlighting the pivotal role these platforms now play in scholars' lives. Additionally, it provides valuable insights for those seeking to harness social media effectively for academic networking and collaborative endeavors.